Memory improving effect of silkworm larva on insulin resistance related cognitive impairment model - Joohyun Hwang; Junhyuk Choi; Seung-Yun Cha; In-Seo Lee; Ji Hye Yoon; Duk Jin Jung; Chang Wook Lee; Seong Ryul Kim; Ji Hae Lee; Byeongyeob Jeon; Ji-Ho Park; Sungho Maeng; et al. (PLoS ONE, 2025)
Hongjam (HJ) is the steamed and freeze-dried powder of larva-stage silkworm ( Bombyx mori ) rich in protein, unsaturated fatty acids, and minerals. Silkworm products have traditionally been used for medical purposes, and their effectiveness in diabetic and neurodegenerative diseases has been studied. In particular, the anti-inflammatory-antioxidant, blood sugar-lowering, and neuroprotective effects are expected to be useful for the prevention and treatment of dementia, especially in a model of dementia related to insulin resistance. Most animal models of Alzheimer’s disease (AD) are based on genetic factors and research based on these models does not explain the pathophysiology of sporadic AD. Therefore, no drug can effectively delay the progression of AD. We hypothesized that HJ may improve cognitive function in an insulin resistance model which is considered one of the causes of sporadic AD. Insulin resistance was induced by a high-fat diet and streptozotocin injection. Additionally, the effect of HJ was tested in in vitro cultured hippocampal slices treated with an N-methyl-D-aspartate antagonist. At the given dose, HJ did not affect on the body weight but lowered blood glucose concentration, improved spatial memory in the Morris water maze and avoidance memory in the passive avoidance tests which was related to hippocampal brain-derived neurotrophic factor. In hippocampal slices, HJ strengthened long-term potentiation, which was suppressed by AP5. Thus, HJ improved cognitive functions in an insulin-resistance related dementia model and may be useful in treating sporadic AD.